2006
DOI: 10.1017/s0012162206001083
|View full text |Cite
|
Sign up to set email alerts
|

Management of scoliosis in Duchenne muscular dystrophy: a large 10-year retrospective study

Abstract: Scoliosis affects 75 to 90% of patients with non-ambulant Duchenne muscular dystrophy (DMD). Spinal surgery is the treatment of choice but the indication varies among centres. Some offer surgery to all non-ambulant patients, irrespective of scoliosis severity. Early surgery has the advantage of targeting DMD when cardiorespiratory function is preserved, but not all patients develop scoliosis. We report our 10-year experience of scoliosis management in 123 patients with DMD who were at least 17 years old at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(43 citation statements)
references
References 31 publications
3
36
0
1
Order By: Relevance
“…Surgery is currently the treatment of choice to arrest the development of scoliosis. However, a recent study of 123 patients suggested that a substantial number of boys require conservative management because of a milder scoliosis, patient choice or cardiorespiratory compromise precluding surgery [1]. This finding supports the potential significance of other techniques of spinal stabilisation in DMD boys, one of which we address in this study.…”
Section: Introductionsupporting
confidence: 82%
See 1 more Smart Citation
“…Surgery is currently the treatment of choice to arrest the development of scoliosis. However, a recent study of 123 patients suggested that a substantial number of boys require conservative management because of a milder scoliosis, patient choice or cardiorespiratory compromise precluding surgery [1]. This finding supports the potential significance of other techniques of spinal stabilisation in DMD boys, one of which we address in this study.…”
Section: Introductionsupporting
confidence: 82%
“…Between 70% and 90% of boys with Duchenne Muscular Dystrophy (DMD) develop progressive scoliosis [1]. Surgery is currently the treatment of choice to arrest the development of scoliosis.…”
Section: Introductionmentioning
confidence: 99%
“…312 Although studies have reported potential advantages of spinal surgery, including increased comfort and sitting tolerance, cosmetic improvement, and pain relief, [313][314][315][316] there is no clearly demonstrated effect of spinal fusion on the natural deterioration of respiratory function in DMD. [316][317][318][319][320][321] There is also debate about improvements in life expectancy, with both lower mortality and no difference in mortality after spinal surgery for DMD having been reported. 317,318,321,322 …”
Section: Assisted Ventilationmentioning
confidence: 99%
“…[316][317][318][319][320][321] There is also debate about improvements in life expectancy, with both lower mortality and no difference in mortality after spinal surgery for DMD having been reported. 317,318,321,322 …”
Section: Assisted Ventilationmentioning
confidence: 99%
“…In neuromuscular scoliosis, the situation is even more complex. Scoliosis 38%-64% [5,6] 20%-94% [7] 63%-90% [8,9] 100% [10] (if injured before adolescent growth spurt)…”
Section: Originmentioning
confidence: 99%